2021
DOI: 10.1246/bcsj.20210379
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Highly Reducible CuO Species by High-Temperature Calcination of a Cu-Al Layered Double Hydroxide: Selective Hydrogenation of Furfural into Furfuryl Alcohol with Formic Acid

Abstract: Highly reducible CuO species were created by the calcination of a Cu-Al layered double hydroxide (CuAl LDH) at 1073 K under air. After this heat treatment, the original layered double hydroxide structure was completely transformed into CuO and CuAl2O4 phases. The synthesized calcined CuAl LDH (calc-CuAl LDH) promoted the catalytic hydrogenation of furfural (FALD) into furfuryl alcohol (FOL) with formic acid (FA) as a hydrogen donor. In the initial stage of the above catalytic reaction, the CuO species in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…It is well known that the calcination of LDH composed of Cu 2+ and Al 3+ at high temperatures up to 1023 K leads to the formation of a CuO and stable spinel CuAl 2 O 4 phase [11] . After calcination of the unsupported CuAl LDH at 1073 K, the powder morphology of CuAlO, which contains CuO and CuAl 2 O 4 , [9,10] appeared similar (Figure 1(c)). Well‐dispersed brucite‐like LDH is visible in the image of 12_CuAl LDH@α‐Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…It is well known that the calcination of LDH composed of Cu 2+ and Al 3+ at high temperatures up to 1023 K leads to the formation of a CuO and stable spinel CuAl 2 O 4 phase [11] . After calcination of the unsupported CuAl LDH at 1073 K, the powder morphology of CuAlO, which contains CuO and CuAl 2 O 4 , [9,10] appeared similar (Figure 1(c)). Well‐dispersed brucite‐like LDH is visible in the image of 12_CuAl LDH@α‐Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 96%
“…It clearly suggests a considerable amount of original CuAl LDH species remained after calcination at 1073 K. Notably, the layered structure of the CuAl LDH phase on the α-Al 2 O 3 surface was not detected in the XRD profile after calcination at 1073 K. In the case of unsupported CuAl LDH, a composition of 54.5 % CuO and 45.5 % CuAl 2 O 4 , with no CuAl LDH remained, was confirmed by LCF after calcination at 1073 K (Figure S4). [10] The treatment of the CuAlO and CuAlO@α-Al 2 O 3 samples for XANES measurement was the same, so it can be concluded that partial rehydration of metal oxide does not occur. It might be said that the Cu 2 + -Al 3 + mixed hydroxide sheets in the matrix of 12_CuAl LDH@α-Al 2 O 3 are more stable under heat treatment than those of the original CuAl LDH.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 93%
See 2 more Smart Citations
“…Mitran et al 5) synthesized a highly efficient Co-Mg-Al mixed oxide derived LDH with welldispersed cobalt species for oxidative dehydrogenation of propane. Another report shows that a highly reducible CuO could be designed by simple calcination of Cu-Al LDH at 1073 K, which then acted as a highly active catalyst towards selective hydrogenation of furfural 13) .…”
Section: Introductionmentioning
confidence: 99%